Synthetic Roof Image Generation using an Extended Gaussian Mixture Model (EGMM) - Agaian, Sos S.; Rao, Shishir P.; Yeole, Rushikesh D.; Hallam, Cory R.A. (IJRDO -Journal of Computer Science Engineering, 2017)
In this paper, we address the problem of generating synthetic images by using a single image, or multiple images, and present an effective Extended Gaussian Mixture Model (EGMM). We apply this method to roof surface images for investigating and identifying differences, changes, and/or structural damage. This technique allows a single impression of a roof to be randomly generated according to input parameters, and can produce new image models using multiple roof images. We further extend GMMs by mixing color textures of the roof images to generate new models. The best fit statistical model image is obtained by finding the minimum pixel distances as compared to the original image. This approach generates very realistic roof models that are useful in performance evaluation and testing, and offers the potential for further research and application in other surface inspection processes.